Identitätspositionierungen der DAX-30-Unternehmen: die sprachliche Konstruktion von Selbstbildern - Burel, Simone (Sprache und Wissen, 2015)
Companies trade not only in raw materials and services but also systematically create factual, non-physical realities, such as identity, as part of their object worlds. To understand the linguistic quest for self-image and corporate identity, this study analyzes symbolic systems in companies’ representational texts, including slogans and mission statements.